Evidence of Long-Distance Coastal Sea Migration of Atlantic Salmon, Salmo Salar, Smolts from Northwest England (River Derwent). - Green, Amy; Honkanen, Hannele M.; Ramsden, Philip; Shields, Brian; Villar-Guerra, Diego del; Fletcher, Melanie; Walton, Silas; Kennedy, Richard; Rosell, Robert S.; O'Maoileidigh, Niall; Barry, James; Roche, William; et al. (Animal Biotelemetry, 2022)
Publication history: Accepted - 10 January 2022; Published online - 26 January 2022 Background Combining data from multiple acoustic telemetry studies has revealed that west coast England Atlantic salmon (Salmo salar L.) smolts used a northward migration pathway through the Irish Sea to reach their feeding grounds. Hundred Atlantic salmon smolts were captured and tagged in May 2020 in the River Derwent, northwest England as part of an Environment Agency/Natural England funded project. Results Three tagged smolts were detected on marine acoustic receivers distributed across two separate arrays from different projects in the Irish Sea. One fish had migrated approximately 262 km in 10 days from the river mouth at Workington Harbour, Cumbria to the northernmost receiver array operated by the SeaMonitor project; this is the longest tracked marine migration of an Atlantic salmon smolt migrating from the United Kingdom. This migrating fish displayed behaviours which resulted in fast northward migration. The remaining two fish were detected on a receiver array operated by a third project: the Collaborative Oceanography and Monitoring for Protected Areas and Species (COMPASS). Conclusion These detections further provide evidence that migration to reach marine feeding grounds of at least a proportion of salmon smolts from rivers draining into the Irish Sea is northerly, though without a southern marine array it is impossible to conclude that this is the only route. The pattern of these detections would not have been possible without the collaborative efforts of three distinct and separately funded projects to share data. Further work is required to fully understand migration trajectories in this species on the west coast of the British Isles. The main Funding bodies for this project were the Environment Agency, Cumbria and Natural England, Cumbria. Additional funding was provided by The Derwent Owners Association and Bowland Game: Isel Fishings.